Activation methods : sonochemistry and high pressure - Goddard, Jean-Philippe; Malacria, Max, 1949-; Ollivier, Cyril; Draye, Micheline; Estager, Julien; Kardos, Nathalie; Chataigner, I. (Isabelle); Maddaluno, Jacques (Chemistry series (ISTE Ltd.), 2019)
"'Activation methods' examines recent improvements in the utilization of ultrasonic waves and pressurized gases to generate reactions. A straightforward method to use, sonochemistry allows chemical reactions to be carried out under ultrasound without the need for external heat, reagents or catalysts -- leading to high yields and the production of a minimum amount of waste. This book presents an overview of the main applications of sonochemistry in green organic chemistry, with an emphasis on texts published within the last few years. High-pressure chemical reactions offer innovative solutions to problems relating to synthesis. They allow access to new products and a further understanding of reaction mechanisms. This book presents the characteristics of hyperbaric activation, which allow the integration of an arsenal of tools for green chemistry, such as the lowering of energy costs and of by-products, as well as the possibility of using substrates that are sterically congested and generally inert"--Page 4 of cover.